2017
DOI: 10.1017/s1368980017001380
|View full text |Cite
|
Sign up to set email alerts
|

Identifying dietary differences between Scotland and England: a rapid review of the literature

Abstract: Objective: Rates of premature mortality have been higher in Scotland than in England since the 1970s. Given the known association of diet with chronic disease, the study objective was to identify and synthesise evidence on current and historical differences in food and nutrient intakes in Scotland and England. Design: A rapid review of the peer-reviewed and grey literature was carried out. After an initial scoping search, Medline, CINAHL, Embase and Web of Science were searched. Relevant grey literature was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The review conducted by Chambers et al ( 14 ) found limited comparisons of diet between Scotland and England in the published literature. The main differences were lower intakes of fruit and vegetables, fibre and water- and fat-soluble vitamins in Scotland, and higher intakes of Ca, salt and processed meat, suggesting a greater emphasis on animal- v .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The review conducted by Chambers et al ( 14 ) found limited comparisons of diet between Scotland and England in the published literature. The main differences were lower intakes of fruit and vegetables, fibre and water- and fat-soluble vitamins in Scotland, and higher intakes of Ca, salt and processed meat, suggesting a greater emphasis on animal- v .…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature ( 14 ) identified significant historical differences in the intake of foods and nutrients, which are likely to have health implications ( 15 ) , between Scotland and England or between Scotland and the Northern regions of England. In Scotland, there was lower fruit and vegetable consumption, lower fibre intake, lower intake of most water- and fat-soluble vitamins and a higher intake of Na.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The combined response rate was 45%, comparable to that of a similar national dietary survey in the UK (47%). 37 Survey weights were used to take the population representativeness into account as much as possible and to match the age and sex distribution of the Barbados population. However, if participants differed systematically from non-participants in ways not accounted for by the survey weights, our estimates of SSB consumption may not be representative of the broader population.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…When the city of Glasgow expanded from a small regional town to become the second city of the empire in the 19th century, there was no food provision service, and the population demand was met with a stereotypic imported diet of white bread, jam and sugary tea, which persisted through habit and regional poverty as ship-building declined, well into the 20th century. Its upshot was widespread stunting, and a dramatic rise in heart disease in Scotland, compared to England, which even now appears to relate in part to lower fruit and vegetable consumption (9).…”
mentioning
confidence: 99%